Transesterification of Tropical Edible Oils to Biodiesel Using Catalyst From Scylla serrata - Risfidian Mohadi; Hesti A. Harahap; Nurlisa Hidayati; Aldes Lesbani (Sriwijaya Journal of Environment, 2016)
Scylla serata shell was decomposed at various temperatures ranging from 700-1100 oC to obtain calcium oxide. Calcium oxide from decomposed Scylla serrata shell was characterized through X-Ray analysis, FTIR spectroscopy, and morphology analysis. Furthermore, decomposed Scylla serrata shell was used as catalyst for transesterification of tropical edible oils to form biodiesel. Biodiesel was characterized through density, viscosity, fatty acid value, and iodine number. The results showed that decomposed Scylla serrata shell at 900 oC could produce calcium oxide similar with standard, which was indicated from X-ray powder diffraction pattern of decomposed shell with JCPDS data. FTIR spectrum showed that main vibration of calcium oxide was observed at 393 cm-1. Morphology analysis using SEM indicated that uniform calcium oxide was obtained after decomposition. The use of decomposed shell as base catalyst for transesterification of tropical edible oils resulted biodiesel with density, viscosity, fatty acid value, and iodine number appropriated with SNI standard.